2018
DOI: 10.1016/j.cell.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genetically Diverse Macrophages Reveals Local and Domain-wide Mechanisms that Control Transcription Factor Binding and Function

Abstract: Non-coding genetic variation is a major driver of phenotypic diversity and allows the investigation of mechanisms that control gene expression. Here, we systematically investigated the effects of >50 million variations from five strains of mice on mRNA, nascent transcription, transcription start sites, and transcription factor binding in resting and activated macrophages. We observed substantial differences associated with distinct molecular pathways. Evaluating genetic variation provided evidence for roles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
210
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(227 citation statements)
references
References 61 publications
15
210
2
Order By: Relevance
“…The basic assumption for MAGGIE is that the allele specificity of epigenomic features is derived from the genetic variation between positive and negative sequences that mutate certain TF binding motifs. This assumption is supported by the findings that motif mutations due to local genetic variation is the major explanation for the gain or loss of TF binding sites (Link et al, 2018a;Kundaje et al, 2015). Considering the importance of transcription factors for other epigenomic features like promoter and enhancer function (Reiter et al, 2017;Spitz and Furlong, 2012), we hypothesized that our framework could help identify motifs mediating both TF binding and other epigenomic features affected by TF binding.…”
Section: Overview Of Maggiementioning
confidence: 71%
See 2 more Smart Citations
“…The basic assumption for MAGGIE is that the allele specificity of epigenomic features is derived from the genetic variation between positive and negative sequences that mutate certain TF binding motifs. This assumption is supported by the findings that motif mutations due to local genetic variation is the major explanation for the gain or loss of TF binding sites (Link et al, 2018a;Kundaje et al, 2015). Considering the importance of transcription factors for other epigenomic features like promoter and enhancer function (Reiter et al, 2017;Spitz and Furlong, 2012), we hypothesized that our framework could help identify motifs mediating both TF binding and other epigenomic features affected by TF binding.…”
Section: Overview Of Maggiementioning
confidence: 71%
“…The difference of representative motif score is a good indicator of the binding activity change of the corresponding TF (Martin et al, 2019;Spivakov et al, 2012). For example, by comparing PU.1 binding in macrophages of C57BL/6J (C57) and BALB/cJ (BALB) mice (Link et al, 2018a), we observed a strongly positive correlation between the score difference of PU.1 (or SPI1) motif and the log fold change of PU.1 binding activity quantified by ChIP-seq reads among 1635 PU.1 binding sites that have SPI1 motif mutations between the two mouse strains (Fig. 1C).…”
Section: Computation Of Motif Score and Motif Score Differencementioning
confidence: 99%
See 1 more Smart Citation
“…However, we identified three transcription factor genes, Cebpb, Mafb and Klf10, that were apparently excluded from all of the cDC. The role of Cebpb in macrophage differentiation is well-recognised [116][117][118] and one of the datasets includes progenitors from Cebpb -/mice [118]. There is evidence of a negative feedback relationship with Irf8 in monocyte-derived DC [119].…”
Section: Dendritic Cell Co-expression Clustersmentioning
confidence: 99%
“…PLAC-seq libraries were prepared for ex vivo microglia, NEUN nuclei and OLIG2 nuclei as previously described with minor modifications (56,88). In brief, purified populations were cross-linked for 15 minutes at room temperature with 1% formaldehyde and quenched for 5 mins at room temperature with 0.2 M glycine (Thermo Fisher Scientific).…”
Section: Proximity Ligation Chip-sequencing (Plac-seq)mentioning
confidence: 99%